Someone Like Me: How Does Peer Parity Influence Participation of Women on Stack Overflow? - Ford Robinson, Denae; Harkins, Alisse; Parnin, Chris (In proceedings of the IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC), 2017)
Stack Overflow is a learning community for software developers to share and solve programming problems with each other. However, women are often deterred from contributing questions or answers. Research external to programming communities suggest the presence of peers can increase activity from underrepresented users in unfamiliar spaces. To investigate the concept of peer parity, we studied how women participate on Stack Overflow and if the presence of more women on a thread enhanced their activity. We found that women who encountered other women were more likely to engage sooner than those who did not. We discuss how these findings can support women in programming communities through peer mentorship and increase engagement.